Interaction of Bile Salts With Lipid Bilayers: An Atomistic Molecular Dynamics Study - Neves, Maria C.; Filipe, Hugo A. L.; Reis, Rita Leones; Prates Ramalho, João P.; Coreta-Gomes, Filipe; Moreno, Maria J.; Loura, Luis M. S. (Frontiers in Physiology, 2019)
Bile salts are biosurfactants crucial for emulsification and intestinal absorption of cholesterol and other hydrophobic compounds such as vitamins and fatty acids. Interaction of bile salts with lipid bilayers is important for understanding their effects on membranes properties. The latter have relevance in passive diffusion processes through intestinal epithelium such as re-absorption of bile salts, as well as their degree of toxicity to intestinal flora and their potential applications in drug delivery. In this work, we used molecular dynamics simulations to address at the atomic scale the interactions of cholate, deoxycholate and chenodeoxycholate, as well as their glycine conjugates with POPC bilayers. In this set of bile salts, variation of three structural aspects was addressed, namely conjugation with glycine, number and position of hydroxyl substituents, and ionization state. From atomistic simulations, the location and orientation of BS inside the bilayer, and their specific interactions with water and host lipid, such as hydrogen bonding and ion-pair formation, were studied in detail. Membrane properties were also investigated to obtain information on the degree of perturbation induced by the different BS. The results are described and related to a recent experimental study (Coreta-Gomes et al., Langmuir, 2015, 31:9097). Differences in macroscopic membrane partition thermodynamics and translocation kinetics are rationalized in terms of the distinct structures and atomic-scale behavior of the bile salt species. In particular, the faster translocation of cholate is explained by its higher degree of local membrane perturbation. On the other hand, the relatively high partition of the polar glycine conjugates is related to the longer and more flexible side chain, which allows simultaneous efficient solvation of the ionized carboxylate and deep insertion of the ring system.